A review of The Serviceberry: Abundance and Reciprocity in the Natural World - Johanna Wilkes (Canadian Food Studies)
In a world that feels overwhelmed by crisis and change, The Serviceberry: Abundance and Reciprocity in the Natural World offers glimmers of hope and connection with the natural world. Through narratives of the delicate and delicious serviceberry, Robin Wall Kimmerer presents a compelling case for creating more place-based connections in an increasingly disconnected world. The stories of farmstands, neighbours, and care for the commons, Wall Kimmerer offers illustrations of how economies of care and reciprocity operate as a form of governance and ways of life. Overall, the Serviceberry offers ways to navigate the complex webs of care and relations between the earth, community, food systems, and ourselves.